Assessing the Economic Feasibility of Assuring Nutritionally Adequate Diets for Vulnerable Populations in Uttar Pradesh, India: Key Findings from 'Cost of the Diet' Analysis (OR21-05-19). (13th June 2019) - Kachwaha, Shivani; Nguyen, Phuong; DeFreese, Michelle; Cyriac, Shruthi; Girard, Amy Webb; Avula, Rasmi; Menon, Purnima
Abstract: Objectives: Uttar Pradesh (UP) is the most populous state with the highest burden of undernutrition in India. Alive & Thrive is working to strengthen behavior change communication (BCC) on diet diversity and quantity, using health systems platforms to deliver maternal nutrition intervention. However, evidence on the accessibility and affordability associated with recommended diets is limited. This study aims to: 1) examine the costs of nutritious foods in local markets, 2) identify inexpensive sources of essential micronutrients which could be promoted through BCC interventions. Methods: Data collection included 24 market surveys and 125 household interviews to obtain food prices and consumption patterns. Cost of Diet (CotD), a linear programing software, was used to estimate the lowest cost for meeting nutrient requirements of 4 types of diet: 1) energy only diet (EO), 2) energy and macronutrient diets (MAC); 3) nutritious diet (NUT-meets recommended intakes for energy and nutrients), and 4) a food habits diet (FHAB-meet energy and nutrient requirements based upon local dietary habits). The diets were compared to identify relative costs and nutrient requirements met. Results: The FHAB diet (USD 90/month for a household of 6 people) was over twice as expensive compared to the energy only diet. EO and MAC diets were affordable for all households, but they indicated inadequate nutrient intakes for vitamins A, C, B-12, folic acid, calcium, and iron. NUT and FHAB diets met all nutrient requirements but were not affordable for the lowest quartile of households. Recommended intakes of Vitamins A, C, B12, and calcium were most difficult to meet. Key foods identified which provided majority of essential macro and micronutrients included wheat flour, buffalo milk, soybean, and spinach. Multiple sources of iron and calcium were identified as affordable and accessible in local markets. Conclusions: Foods available in local market are sufficient for households to obtain recommended intakes of macro- and micronutrients. Economic constraints and dietary habits are key barriers to achieve a nutritious diet. Practical, habitual diet-related behavior change communication to middle and high-income households and additional social protection for poorer households could improve optimal nutrient intakes. Funding Sources: Bill & Melinda Gates Foundation through POSHAN, led by International Food Policy Research Institute.